Characteristics of Land Use and Plant Production in Transcarpathia - Taraczközi, Kamilla (Acta Agraria Debreceniensis, 2005)
The character of plant cultivation and animal husbandry in different parts of Transcarpathia, are mostly determined by the location of a given region. Usually, four zones are delineated: 1. lowlands; 2. foothills and volcanic remains zone; 3. inter-mountainous subsidence and deep valley; 4. mountain zone. In county this zone divides quite visibly. By studying the soil, climatic conditions and plants, it is not difficult to see that the vertical zones play a major role in their characteristics and formations. If we go from lower to higher elevations, we can observe the qualitative difference in the environment and, of course, in the character of agriculture. Environmental pollution is a global problem of our age. In agriculture, the most important thing is to preserve the ideas of sustainable development, because only these can ensure the protection of production resources, which will ensure the continuous production of agricultural products. Present environmental conditions pose a more problematic challenge to agriculture.